FIRST OCCURRENCE OF THE GENUS ARVERNOCEROS HEINTZ, 1970 FROM THE LATE EARLY PLEISTOCENE OF ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Remains of the large-sized deer Arvernoceros from the sites of Madonna della Strada and Selvella (late Early Pleistocene, central Italy) are described. At present, these records represent the first occurrence of this genus in Italy.These remains show morphological and morphometric characters comparable to the species Arvernoceros giulii and quite different from other Early Pleistocene large-sized deer. A. giulii was a typical species of a savannah-like environment and it seems to have evolved on the plains of central Asia. The dispersal of the species into Western Eurasia is probably caused by transformations of the eastern Paratethys during the Early Pleistocene and its occurrence in Italy may also have been favoured by climatic changes and by the geographical position of the peninsula.
Keywords: Arvernoceros; Postcranium; Morphology; Morphometry; Early Pleistocene; Italy